Perilaku Pembakaran Sampah Terbuka: Persepsi Sosial Komunitas RW 01 Desa Darmasari - Siti Afifah Sahasika; Muhammad Kayyis Firasy Rizqy; Ningrum Cahyani; Elisa Kurniadewi (Yayasan Literasi Sains Indonesia, 2026)
Open waste burning (OWB) remains a significant challenge in developing nations, particularly in rural areas characterized by limited infrastructure and formal management services. This study aims to analyze how OWB practices in RW 01 Darmasari Village are constructed and reproduced as a normalized social practice. Utilizing a qualitative approach with Interpretative Phenomenological Analysis (IPA), the research explores the subjective experiences of six purposively selected participants. Pierre Bourdieu’s Social Practice Theory serves as the analytical lens to examine the interplay between habitus, capital, and field. The study identified three central themes (1) community awareness of the impact of waste burning, which is considered minor, (2) waste burning as a normalized collective habit, (3) burning as a practical choice due to the absence of waste management services. The findings conclude that OWB persists because it has become an internalized habitus perceived as a form of domestic independence in maintaining rural cleanliness. Behavioral change cannot be achieved through technical infrastructure alone; it requires community-based interventions that address social norms and risk perceptions.